An intercomparison of maternal and neonatal outcomes between COVID-19 infected and non-infected antenatal patients - Kharakwal, Sushila; Gautam, Rajni; Mishra, Prerana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Our study aimed to evaluate the severity of COVID-19 infection and pregnancy complications in pregnant women with and without COVID-19, and its impact on maternal and neonatal morbidity and mortality at a tertiary care hospital in India. Methods: The research is a prospective, comparative, and observational study on antenatal patients with confirmed COVID-19 infection status. Results: Results showed preterm labour was the most common maternal complication among COVID-19 infected pregnant women, leading to various complications and long-term developmental delays. Maternal mortality was significantly higher among COVID-19 positive patients compared to non-infected patients. Although neonatal mortality rates were not significantly impacted, morbidity in terms of preterm birth increased among neonates born to COVID-19 positive mothers, resulting in complications like respiratory distress syndrome, intraventricular haemorrhage, and sepsis. Conclusions: our study found increased overall mortality in antenatal patients infected with COVID-19 compared to non-infected patients, consistent with previous studies. The increased mortality rates may be attributed to severe respiratory complications and co-morbidities associated with COVID-19 infection in pregnant women.